Agrarian Conflict in Yogyakarta Special Region: Investigating Conflict Resolution in the Use of Sultanate Ground in Danurejan - Wirayuda, Edwan Nizar; Efendi, David (GoAcademica Research & Publishing, 2024)
The aim of this research is to determine efforts to resolve street vendors' conflicts regarding the use of Sultan Ground in the Jalan Representative area. The method in this research uses a qualitative case study approach as a method to understand the significance of social problems. The data collection technique in this research uses primary data involving sources from the Yogyakarta City Land and Spatial Planning Service, the Kraton Panitikismo, the Yogyakarta Legal Aid Institute, the Representative Communication and Coordination Forum, and the DIY Land Care Forum for the sake of the Republic of Indonesia. Meanwhile, secondary data uses relevant research, documents, and mass media. The collected data is analyzed interactively with three stages of analysis, including: First, data reduction, namely collecting data. Second, data presentation, namely describing research data that has been successfully reduced. Third, drawing conclusions. The results of this research show that the indicators for conflict de-escalation, conflict negotiation, conflict resolution, and conflict reconciliation are not going well because each indicator can be concluded not to have precise results and could even have the potential to give rise to further conflict. The absence of space for dialogue means that traders are not able to argue and try to reach an agreement that can be agreed to by both parties. Apart from that, there was no further dialogue from the government or producers with the traders after the relocation.